1983
DOI: 10.1017/s0140525x00016861
|View full text |Cite
|
Sign up to set email alerts
|

Is blindsight an effect of scattered light, spared cortex, and near-threshold vision?

Abstract: Blindsight is the term commonly used to describe visually guided behaviour elicited by a stimulus falling within the scotoma (blind area) caused by a lesion of the striate cortex. Such “vision” is normally held to be unconscious and to be mediated by subcortical pathways involving the superior colliculus. Blindsight is of considerable theoretical importance since it suggests that destriate man is more like destriate monkey than had been previously believed and also because it supports the classical notion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(161 citation statements)
references
References 117 publications
6
153
2
Order By: Relevance
“…They will then ignore the weaker internal responses generated in the affected areas. Criterion shifts under these neurological conditions have been invoked (12,13) and actually observed (14).…”
Section: Modeling the Data And Discussionmentioning
confidence: 90%
“…They will then ignore the weaker internal responses generated in the affected areas. Criterion shifts under these neurological conditions have been invoked (12,13) and actually observed (14).…”
Section: Modeling the Data And Discussionmentioning
confidence: 90%
“…He shows that belief in the hypothesis of perception without awareness was widespread prior to Ericksen's (1960) influential critique, after which confidence in the hypothesis was slow to recover. He did not foresee that, shortly after the publication of his second book on subliminal perception (Dixon, 1981), similar concerns would again throw the field into controversy (Campion, Latto, & Smith, 1983;Holender, 1986;Merikle, 1984;Schacter, 1989;Shanks & St. John, 1994). A third wave of confidence has arrived.…”
Section: A History Of Controversymentioning
confidence: 99%
“…Thus, we confirmed that the visual field corresponding to the lesion anatomically estimated by the postoperative MRI was functionally affected. In our previous study, we also examined the possibility that the monkeys used light scattering of the visual stimuli presented in the affected visual field (Campion et al, 1983;Gross et al, 2004). We examined whether they could respond to a 1.52°v…”
Section: Methodsmentioning
confidence: 99%